Brazil's new national policy on solid waste: challenges and opportunities - Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Jabbour, Charbel José Chiappetta [UNESP]; Sarkis, Joseph; Govindan, Kannan (Springer Nature, 2013)
Brazil, one of the world's largest developing countries, has recently introduced a new solid waste management regulatory policy. This new regulatory policy will have implications for a wide variety of stakeholders and sets the stage for opportunities and lessons to be learned. These issues are discussed in this article. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Brazil; National policy on solid waste; Sustainability